Chinese expert consensus on the clinical diagnosis and treatment of advanced breast cancer (2018). (25th July 2020) - Xu, Binghe; Hu, Xichun; Feng, Jifeng; Geng, Cuizhi; Jin, Feng; Li, Hongyuan; Li, Man; Li, Qing; Liao, Ning; Liu, Donggeng; Liu, Jian; Liu, Qiang; et al.
Abstract : Breast cancer is the most common malignant tumor among women in the world. In 2005, there were approximately 272, 000 new cases diagnosed and more than 70, 000 deaths from breast cancer in China. Of the patients who are newly diagnosed with breast cancer each year, approximately 3% to 10% have distant metastases at the time of diagnosis. Of those who have early stage disease at diagnosis, from 30% to 40% will develop advanced breast cancer. The 5‐year survival rate for patients with advanced breast cancer is only 20%, and the median overall survival (OS) is 2 to 3 years. Although advanced breast cancer is still difficult to cure, physicians can relieve clinical symptoms, improve quality of life, and further prolong survival through the development of new drugs and the optimization model of treatment. Patients with advanced breast cancer have their own preferences in the choice of treatment options. Moreover, there is no standard recommendation for the treatment of refractory breast cancer after multiline therapy. To offer a reference for clinicians, a Chinese expert group has analyzed, summarized, and discussed related research data on the diagnosis, treatment, and prognosis of inoperable, locally advanced breast cancer and recurrent or metastatic breast cancer and has developed the Chinese expert consensus on the clinical diagnosis and treatment of advanced breast carcinoma (2018). Abstract : There is no standard recommendation for the treatment of refractory breast cancer after multiline therapy. To offer a reference for clinicians, a Chinese expert group has analyzed, summarized, and discussed related research data on the diagnosis, treatment, and prognosis of inoperable, locally advanced breast cancer and recurrent or metastatic breast cancer and reports the development of a Chinese expert consensus on the clinical diagnosis and treatment of advanced breast carcinoma.